S-BESE: Strategy for Improving the Quality of Life for Coastal Area Communities in West Kalimantan - Sarjana, Sri; Claudia, Sindy Allaam; Ramadhina, Assyifa Tasma; Suyanti, Lilis (BRIN Publishing (Penerbit BRIN), 2024)
The coastal area of West Kalimantan has a wealth of marine and river fishery resources that have the potential to be utilized optimally, including fishing, conservation, port activities, marine cultivation, coastal tourism, and water. Various problems in coastal areas that need to be prioritized to provide solutions include the occurrence of illegal fishing, damage to coral reef ecosystems and mangroves, coastal abrasion, not yet optimal development of ponds where utilization only reaches 40% of their potential, natural disasters which result in increased poverty and ecosystem damage, as well as the growth of corruption and injustice. The number of people living in poverty has been steadily increasing at an average rate of 6.86% over the past three years, reaching 353,350 individuals in 2023. This research aims to develop coastal areas, creating local economic development innovations to reduce poverty, unemployment, and inequality and preserve natural resources. The method developed in this study was carried out descriptively and qualitatively by developing an in-depth analysis through SWOT. The results provide solutions for improvements and innovations, which include implementing a blue economy by utilizing the modernization of fishing gear, developing a paradigm shift from land to water resources, and producing garbage filters in rivers so they do not wash away into the sea. This study will improve the quality of life economically and socially while maintaining the ecology in coastal areas.